Pathogen-Associated Molecular Patterns Initiate Inflammation and Perturb the Endocrine Function of Bovine Granulosa Cells From Ovarian Dominant Follicles via TLR2 and TLR4 Pathways - Martin Sheldon (Endocrinology, 2013)
Bacterial infections of the uterus or mammary gland commonly cause disease and infertility byperturbing growth and steroidogenesis of the dominant follicle in the ovary of cattle. Cells of theinnate immune system use Toll-like receptors TLR2, TLR4 and TLR5 to recognize pathogen-associatedmolecular patterns (PAMPs) expressed by bacteria, leading to activation of MAPK and NFBpathways, and production of inflammatory cytokines such as IL-1 and IL-6, and the chemokineIL-8. The present study tested whether granulosa cells from dominant follicles have functionalTLR2, TLR4 and TLR5 pathways. Supernatants of primary bovine granulosa cells accumulated IL-1,IL-6andIL-8whentreated for 24hwithPAMthat binds TLR2 or LPS that binds TLR4, but not flagellinthat binds TLR5. Granulosa cell responses to PAM or LPS were rapid, with increased phosphorylationof p38 and ERK1/2 within 30 min and increased abundance of IL6, IL1B, IL10, TNF, IL8 andCCL5 mRNA after 3 h treatment. Accumulation of IL-6 in response to PAM and LPS was attenuatedusing siRNA targeting TLR2 and TLR4, respectively. Furthermore, treating granulosa cells withinhibitors targeting MAPK or NFB reduced the accumulation of IL-6 in response to LPS or PAM.Treatment with LPS or PAM reduced the accumulation of estradiol and progesterone, and thePAMPs reduced granulosa cell expression of CYP19A1 mRNA and protein. In conclusion, bacterialPAMPs initiate inflammation and perturb the endocrine function of bovine granulosa cells fromdominant follicles via TLR2 and TLR4 pathways.